THE EFFECT OF LEARNING EXPERIENTIAL METHOD TOWARD LEARNING WRITING ABILITY OF CREATIVE POETRY BASED ON PERSONAL EXPERIENCE OF SEVENTH GRADE STUDENTS OF SMP PEMBINA OF PALEMBANG - Wardiah, Dessy (Jurnal Dosen Universitas PGRI Palembang)
Abstract This study aims to determine and describe the influence model of experiential learning to creative poetry writing ability based on personal experience of the class student student of Pembina Palembang. The method used in this study is an experimental method with a pretest-posttest control group design. Samples are 39 students of VII.1 class as an experimental class and VII. 4 class which consist of 34 students as the control class. Technique for collecting used in this study was the written test. The results of study was there is significant influence of experiential learning method toward students ability in writing creative poetry based on personal experience of seventh grade students of SMP Pembina Palembang", The result of t-tests showed that the value of t-obtained was higher than t-table (2.95 higher than 1.66) Keywords: Learning, model of experiential learning, writing poetry, personal experience